Fantastic Illusions : Die Sehnsucht im Bild zu sein. - De Jaeger, Christophe; Vermeulen, Pieter; Zhou, Lisa (Shanghai : Shanghai eArts Shanghai, 2009)
De Clercq, Anouk ; Stolle, Bart ; Crew ; Claerbout, David ; de Beeck, Hans Op ; Voet, Heidi ; Ervinck, Nick ; Deprez, Olivier ; Tale of Tales ; Vosters, Vadim ; Bernard, Yves ; Antoine, Yannick ; Chen, Jenova ; Hu Jie Ming ; Lo, Teddy ; Peng Yun ; Wu Juehui ; Aaajiao (Xu Wenkai)
Fantastic Illusions-Media Art Exhibition of Chinese And Belgian Artists, Broelmuseum Kortrijk, MOCA (Museum of Contemporary Art) Shanghai. 2009-09-13. 2009-11-14. 2009-10-11. 2010-02-07
boek
Keywords: België; China